2018
DOI: 10.1186/s12544-018-0306-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the economic and environmental impacts of urban food systems for public school canteens: case study of Great Lyon region

Abstract: Purpose: Urban logistics is a subject that interests both city planners and researchers. Although many works are found in non-food distribution, food-based logistics is less studied in an urban context, and sustainability issues of urban food systems remain little analysed, but it is a crucial element for local public authorities. This paper proposes a methodology for assessing scenarios of advanced urban food logistics; more precisely to answer the question of how school canteen distribution scenarios can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 46 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…Along with the results of other studies in various urban contexts [1,2,13,31,41,43,53], our research has demonstrated the benefits-in a quantifiable (and qualitative as well) manner-of a mixed passenger and freight urban system in the Venice Lagoon in terms of increased urban performance and sustainability (optimization of the existing transport capacity). In particular, the case study has focused on peripheral areas (core-periphery connections), where few studies have been conducted so far elsewhere and never so in Venice.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Along with the results of other studies in various urban contexts [1,2,13,31,41,43,53], our research has demonstrated the benefits-in a quantifiable (and qualitative as well) manner-of a mixed passenger and freight urban system in the Venice Lagoon in terms of increased urban performance and sustainability (optimization of the existing transport capacity). In particular, the case study has focused on peripheral areas (core-periphery connections), where few studies have been conducted so far elsewhere and never so in Venice.…”
Section: Discussionsupporting
confidence: 70%
“…Following some methodologies proposed in the literature [10,51,53], we develop an original scenario-building approach to assess proposed mixed transport services consisting of:…”
Section: Data Analysis and Methodsmentioning
confidence: 99%
“…Palacios-Argüello et al [12] propose a method to assess the economic and environmental performance of food distribution schemes for public school canteens in Lyon, France. The results reveal the importance of planning the logistics distribution system in a way that both reduces the negative impacts of food distribution and is economically feasible.…”
Section: Planning For Efficient Metropolitan Freight Systemsmentioning
confidence: 99%
“…This Topical Collection (TC) seeks to provide a better scientific foundation for the integration of freight into city planning. [7], Campbell et al [5], Pitera et al [13] and Aditjandra and Zunder [1] focus on planning related to local freight needs; Palacios-Argüello et al [12], Gonzalez-Calderon et al [10] and Fossheim and Andersen [9] study the characteristics and requirements of planning for freight in metropolitan areas; Buldeo Rai et al [4] and Arnold et al [3] focus on innovations related to urban freight, while Le Pira et al [11] study the interaction between freight stakeholders when finding a policy package in common agreement.…”
mentioning
confidence: 99%
“…To this end, it is necessary to explore the influence of parameters of the last mile routing system on the character of forming the added value of goods as a result of transportation. In this case, it is advisable to apply a value assessment of consequences of the implementation of transportation process within the framework of the last mile by analogy to studies [27,28].…”
Section: Determining the Character Of Demand For Goods Transportatmentioning
confidence: 99%